Comparison of Functional Outcome and Quality of Life in Patients With Idiopathic Scoliosis Treated by Spinal Fusion. Issue 19 (May 2016) - Fan, Hengwei; Wang, Qifei; Huang, Zifang; Sui, Wenyuan; Yang, Jingfan; Deng, Yaolong; Yang, Junlin
Abstract : Abstract: Longer spinal fusions have been shown to result in improved deformity correction; however, loss of normal flexibility in the fusion area should not be ignored. Current consensus was to achieve a shorter fusion in primary surgery, with the goal of preserving as much of the distal motion segment as possible. However, the correlation between the length of fusion and functional outcome remains controversial. To the best of our knowledge, a previous study has demonstrated the function outcomes and the differences in HRQoL with specific fusion levels. In this cross-sectional study, 172 patients (mean age, 17.8 y) with idiopathic scoliosis treated by spinal fusion (mean time since surgery, 29.7 mo) were included to measure lumbar spine mobility and quality of life using validated outcome instruments in the study population. Patients were assigned to 5 groups according to the lower instrumented vertebra (LIV) level: group A (fusion above L2) 26 patients; group B (fusion to L2) 21 patients; group C (fusion to L3) 46 patients; group D (fusion to L4) 53 patients; and group E (fusion to L5) 26 patients. At each follow-up, patients were asked to complete the Scoliosis Research Society 22 (SRS-22) Questionnaire. Lumbar mobility was assessed using a dual digital inclinometer. Average spinal range of motion (ROM) was 41.4 degrees (SD, 20.7), forward flexion was 29.2 degrees (SD, 15.0), and backward extension was 12.2 degrees (SD, 9.5). The total spinal range of motion and forward flexion dropped noticeably as the LIV got more distal. Statistically significant between-group differences (1-way ANOVA) were found for ROM ( P < 0.001), forward flexion ( P < 0.001), or backward extension ( P < 0.001). The motion segments preserved significantly correlated with ROM ( r = 0.76, P < 0.001), ROMF ( r = 0.76, P < 0.001), and ROME ( r = 0.39, P < 0.001). However, no significant between-group differences was found for each domain of SRS-22 questionnaire. The motion segments preserved strongly correlated with lumbar mobility. Less fusion levels can preserve better lumbar flexibility by keeping more motion segments.